RP-HPLC Analysis of Quercetin in the Extract of Sambong (Blumea balsamifera (L) DC) Leaves - Joanna V. Toralba; Noel S. Quiming; Jocelyn SB Palacpac (Science Diliman, 2015)
Blumea balsamifera (L) DC, known in the Philippines as sambong, is an herb valued for its health benef its especially in the management of urolithiasis. Various phytochemicals, including flavonoids such as quercetin, have been determined in sambong leaves. A reversed-phase high-performance liquid chromatographic method (RP-HPLC) was developed for the quantitative determination of quercetin in the methanol extract of sambong leaves obtained from Leyte, Cotabato, and Nueva Ecija, Philippines. The methanol extracts of sambong were prepared by maceration followed by rotary evaporation. The solid phase extraction (SPE) for the sample cleanup involved the use of a C18 SPE packing, a 0.5-mL sample load (50 mg/mL solution), and elution with 4-mL of 80:20 Methanol:0.5% H3PO4. The HPLC conditions for the determination of quercetin involved the use of a C18 4.6-mm x 250-mm column maintained at 30°C, 254-nm UV detection, and a mobile phase composition of 25 parts methanol and 75 parts mixture of 0.5% H3PO4 and 0.2% triethylamine with a 1 mL/min flow rate in gradient elution. A good linearity at the concentration range of 3.72–124 μg/mL of quercetin standard (r2=0.9989) was observed with the limits of detection (LOD) and quantitation (LOQ) at 0.68 ng/mL and 2.28 ng/mL, respectively. The intra-day (n=5-) and inter-day (n=3) precision values were satisfactory (%RSD <2%). The recovery eff iciency of the SPE sample cleanup step, which was checked by spiking sambong solution with quercetin standard, was 102.41%. The quercetin contents are 0.2337mg, 0.1350mg, and 0.2940mg per gram of the powdered dried leaves of sambong from Nueva Ecija, Cotabato, and Leyte, respectively. This is the f irst report of quercetin content in the leaves of sambong collected from the Philippines.